Gender in mental health: Relationship of spirituality, social support, and COVID-19-related fear among heterosexual and LGBTQ+ youth - Alibudbud, Rowalt (Frontiers in Sociology, 2023)
Introduction The youth is a vulnerable population to COVID-19-related fear. Among them, those with LGBTQ+ identities are at higher risk. Given the posited protective effects of spirituality and social support on fear, this study explored their effects on COVID-19-related fear among heterosexual and LGBTQ+ youth. Materials and methods This cross-sectional study recruited 137 respondents Filipinos aged 18–30 years old. The respondents answered a survey containing a sociodemographic questionnaire, 12-items Multidimensional Scale of Perceived Social Support (MSPSS), 20-items Core Dimensions of Spirituality Questionnaire (CDSQ), and 7-items Fear of COVID-19 Scale (FCS). After, the data were analyzed using means, frequencies, Mann-Whitney U-tests, and correlation coefficients. Results Social support from friends was negatively correlated with COVID-19-related fear among heterosexual respondents, R = −0.219, p = 0.029. Search for meaning positively correlated with COVID-19-related fear among LGBTQ+ respondents, R = 0.395, p = 0.016. Heterosexual respondents also have a higher belief in God (U = 1,004, p < 0.001) and feelings of security (U = 1,110.5, p < 0.001) than their LGBTQ+ counterparts. Discussion These findings suggest that social support from friends is protective against COVID-19-related fear among heterosexual youth but not among LGBTQ+. In addition, a high search for meaning can heighten COVID-19-related fear among LGBTQ+. Finally, these findings can be explained by the higher rates of discrimination against LGBTQ+ than heterosexual youth. Thus, gender-responsive mental healthcare is needed to address the youth's fears as society recovers from the pandemic.